Inertial splitting algorithms for nonlinear operators of pseudocontractive and accretive types. (4th March 2023) - Luo, Yinglin; Tan, Bing; Li, Songxiao
ABSTRACT: In this paper, inertial splitting algorithms for nonlinear operators of pseudocontractive and accretive types are proposed. Weak and strong convergence theorems are established in uniformly convex and q -uniformly smooth Banach spaces. Numerical examples are given to illustrate the effectiveness of our proposed algorithms.